Determination of tetracycline hydrochloride in some pharmaceutical products using flow injection spectrophotometric technique - Baban, Shirwan Omer; Ali, Rasul Jameel (Sulaimani Journal for Pure and Applied Sciences, 2016)
A simple, rapid, and sensitive flow injection spectrophotometric system for determination of tetracycline hydrochloride (TCH) in pharmaceutical products. The method is based on diazotization of 2-aminopyridine and subsequent coupling with tetracycline hydrochloride in alkaline medium. The formed azo-dye showed maximum absorbance at 388 nm and the calibration curve in the linear range of 25.0-150.0 µg/ml of tetracycline hydrochloride with correlation coefficient 0.9988, while the detection limit was 10 µg/ml and sample frequency 123 samples/hour. The accuracy and precision data for determination of TCH by flow injection analysis method for triplicate injection at three concentration levels(25, 80 and 150 µg/ml) the relative standard deviation (RSD %) are 1.04, 0.247 and 1.75%, and relative error percent (E rel ) are -3.92, +1.06 and -1.9%. The proposed method was successfully applied to the determination of tetracycline hydrochloride in pharmaceutical products. The results obtained were in good agreement with those obtained by reference method.
Keywords: tetracycline hydrochloride; 2 aminopyridine; flow injection spectrophotometric